The accountant's contribution in tax planning: a case study on the production and commercialization of Arla 32 in a business group in the municipality of Araújos-MG (Research, Society and Development, 2023)
Tax planning, when carried out in accordance with the law, has the main objective of reducing costs for companies, Taxpayers have to organize their businesses in a way that suits them as is their constitutional right, as long as they obey the legal limits. The objective of the present study is to verify if the commercialization of Arla 32 becomes more lucrative due to implementation of the tax reorganization strategy. A case study was performed in a business group from the town of Araújos-MG, of which they are part of an industry that produces Arla 32 and opt for the Simples Nacional tax regime, and a fuel and lubricant retail station, opting for the Real income tax regime, which sells the previously mentioned product to the final consumer. To reach the proposed objective, the authors proposed the application of a strategy which involves the purchase of raw materials, from which results are calculated over a 12 month period, with the intention of comparing the current reality of the business group, to what their reality would be with the application of the author's proposed strategy. The results of the investigation point to a relevance impact on the viability of the results of the companies, being possible to verify how much the tax reorganization is essential for the competitiveness of the companies in the market.